Prevalence and prognostic significance of malnutrition risk in patients with tuberculous meningitis - Guo, Can; Liu, Ke-Wei; Tong, Jing; Gao, Meng-Qiu (Frontiers in Public Health, 2025)
The residual risk of mortality or neurological disability is high in tuberculous meningitis (TBM), but there are not many effective treatments for TBM. Malnutrition is a modifiable risk factor for patients with tuberculous, however, the relationship between nutritional risk and neurological prognosis is not clear. In the present study, we aimed to explore the association between malnutrition risk and neurological outcome in patients with TBM.Methods: A retrospective cohort study was conducted from December 2010 to January 2021. Malnutrition risk were evaluated by nutritional scales, including controlling nutritional status score (CONUT), geriatric nutritional risk index (GNRI), and prognostic nutritional index (PNI). The primary outcome was poor recovery measured by modified Rankin Scale at 1 year follow-up. Malnutrition risk was estimated and the association between malnutrition and follow-up outcome was analyzed.Results: A total of 401 participants were analyzed in the study. According to CONUT, GNRI, and PNI, 299(74.56%), 231(57.61%), and 107(26.68%) patients were with malnutrition risk on admission. At 1 year follow-up, a total of 115 patients (28.67%) were with poor recovery. After adjustment for confounding factors, the association between moderate malnutrition (OR=1.59, 95% CI 1.00-3.59, P=0.050), or severe malnutrition (OR=3.76, 95% CI 1.03-12.63, P=0.049) estimated by CONUT and was significantly associated with poor outcome. For each point increase in COUNT score (OR=1.12, 95% CI 1.00-1.27, P=0.059), the odds of poor functional recovery increased by 12%.Conclusions: Malnutrition in TBM patients was related to an increased risk of poor neurological recovery in the long-term follow-up. Our study stressed the importance for assessing malnutrition in TBM patients.